Bacillus anthracis spore interactions with mammalian cells: Relationship between germination state and the outcome of in vitro - Gut, Ian M (BioMed Central, 2011)
BACKGROUND: During inhalational anthrax, internalization of Bacillus anthracis spores by host cells within the lung is believed to be a key step for initiating the transition from the localized to disseminated stages of infection. Despite compelling in vivo evidence that spores remain dormant within the bronchioalveolar spaces of the lungs, and germinate only after uptake into host cells, most in vitro studies of infection have been conducted under conditions that promote rapid germination of spores within the culture medium. RESULTS: Using an in vitro model of infection, we evaluated the influence of the germination state of B. anthracis spores, as controlled by defined culture conditions, on the outcome of infection. Spores prepared from B. anthracis Sterne 7702 germinated in a variety of common cell culture media supplemented with fetal bovine serum (FBS) while, in the absence of FBS, germination was strictly dependent on medium composition. RAW264.7 macrophage-like cells internalized spores to the same extent in either germinating or non-germinating media. However, significantly more viable, intracellular B. anthracis were recovered from cells infected under non-germinating conditions compared to germinating conditions. At the same time, RAW264.7 cells demonstrated a significant loss in viability when infected under non-germinating conditions. CONCLUSIONS: These results suggest that the outcome of host cell infection is sensitive to the germination state of spores at the time of uptake. Moreover, this study demonstrates the efficacy of studying B. anthracis spore infection of host cells within a defined, non-germinating, in vitro environment.